The Effective Commands Used by the Teacher in English Teaching at SMA - Octaviani, Ni Luh Ade (Universitas Pendidikan Ganesha, 2022)
This study aimed at investigating the types of students’ disruptive behavior, the types of commands used by the English teacher, and analyzing the effective commands used by the English teacher to overcome students’ disruptive behavior. The method used in this study was descriptive method in which the data were described under the reality to answer the purpose of this research in finding section and draw the conclusion. The findings of this study revealed that students’ disruptive behaviors that appeared during the learning process could be categorized as The Immature and Well to Do. In handling both types of students' disruptive behavior, the teacher used several commands; those were Interrogation Commands, Regular Commands, Question Commands, Don’t Commands, Indirect Command, and Other Commands. Several commands that were effective were Interrogation Command, Question Command, Indirect Command, and Other Commands.